Higher fasting plasma FGF21 concentration is associated with lower ad libitum soda consumption in humans. Issue 4 (22nd June 2021) - Basolo, Alessio; Hollstein, Tim; Shah, Mujtaba H; Walter, Mary; Krakoff, Jonathan; Votruba, Susanne B; Piaggi, Paolo
ABSTRACT: Background: The hepatokine fibroblast growth factor 21 (FGF21) influences eating behavior and sugar consumption in rodent models. However, whether circulating FGF21 concentration is associated with food and soda intake in humans is still unclear. Objective: We investigated whether fasting plasma FGF21 concentration is associated with objective measures of ad libitum food intake and soda consumption. Methods: Healthy individuals [ n  = 109; 69 men, aged 34 ± 10 y; BMI (kg/m 2 ): 30.4 ± 7.7; body fat by DXA: 30.5% ± 8.9%] with available plasma for hormonal measurements participated in an inpatient cohort study to objectively quantify ad libitum food and soda intake for 3 d using an automated and reproducible vending machine paradigm. Fasting plasma FGF21 concentration was measured by ELISA prior to ad libitum feeding. Results: Fasting FGF21 concentration was inversely associated with daily soda intake ( R = −0.22, P  = 0.02 adjusted for demographics and anthropometrics), such that an interindividual difference of 200 pg/mL was associated with an average lower soda consumption by 68 kcal/d. Conversely, no associations were observed with total daily energy intake or macronutrient intake (all P  > 0.17). Conclusions: Higher plasma fasting FGF21 concentration is associated with lower ad libitum soda intake. Although this inverse correlation does not imply causation, the present results support the putative role of FGF21 in the reward pathways regulating sugar consumption in humans. This trial was registered at www.clinicaltrials.gov as NCT00342732.